Physical performance of Brazilian rugby players from different age categories and competitive levels - Kobal, R.; Nakamura, F. Y.; Moraes, J. E.; Coelho, M.; Kitamura, K.; Cal Abad, C. C.; Pereira, L. A.; Loturco, I. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to compare the anthropometric characteristics and physical capacities (vertical jumping, speed, agility, and endurance abilities) among different age categories of Brazilian rugby players from the same high-level club and to compare their respective data with those obtained from the national team players. Eighty-eight men Brazilian rugby players from 4 different age categories were divided into 4 different groups (i.e., under-15 [U-15], under-17 [U-17], under-19 [U-19], and professional senior team [PRO]) and a group composed of players from the Brazilian national team (NAT). Anthropometric measures (i.e., height and body mass), squat jump (SJ) and countermovement jump (CMJ) tests , 2 agility tests (change of direction [COD] and proagility), 40-m sprinting, and the Yo-Yo endurance test (level 1) were compared among the groups using an analysis of covariance (multivariable multivariate analysis of covariance) with the body mass as a covariate. The NAT group demonstrated significantly greater performances in all variables compared with the U-15, U-17, U-19, and PRO groups (p = 0.05). Moreover, the PRO group demonstrated better performances in vertical jumping assessments (i.e., SJs and CMJs) and agility tests (i.e., COD and proagility) than the younger categories (p = 0.05). Finally, except for the U-15 group, no significant differences were found between the young age-categories in sprint and endurance capacities. These findings show that, throughout the maturation process, rugby players improve their muscle power and agility abilities without presenting significant increases in endurance and sprinting capacities. Importantly, this does not hold true for players from the NAT group, who presented superior performance in all assessed physical variables (in comparison with the younger age and PRO categories).